Women in African agriculture integrating women into value chains to build a stronger sector - Georgina Wambui Njiraini; Marther W. Ngigi; Evelyn Baraké (University of Bonn, Center for Development Research (ZEF), 2018)
Women are under-acknowledged participants in Africa's agriculture and food sector, supplying a large share of the labour, but facing significant obstacles, including unequal access to land, traditional division of labour, restrictions on mobility, unequal educational attainment, financial exclusion, and gender norms. As a result, women are being constrained to lower productivity jobs and earning less than men. Their underrepresentation persists all along agricultural value chains. These inequalities translate into lower welfare outcomes for women in addition to inefficient productivity gaps with negative consequences for food security on the continent. Technical and institutional innovations in agricultural value chains must therefore be developed and implemented in a way that considers the particular constraints faced by women in agriculture in order to be fully effective and to avoid further solidifying gender roles and gaps. These could include suitable labour-saving technologies, financial innovations, mechanisms for collective action, and an improved access for women to extension services.
Keywords: J16; Q00; Q13; Q15; Q16; 330; women; gender; agriculture; value chains; productivity; inequality